Farmers’ Perception on Grey-headed Lapwing (Vanellus cinereus) Existence in Paddy Field Surrounding Gifu University, Japan (Applied Research in Science and Technology, 2022)
In agriculture practices, besides animal, human activity belongs to the enemy of Grey-headed Lapwing (Vanellus cinereus). This study aims to analyze the farmers’ perception on Grey-headed Lapwing existence in paddy field surrounding Gifu University, Japan. There are 10 farmers who are work in the research area. All of them are farmers. Descriptive method was used in this study, the data were collected with questionnaire. The finding show that farmers ignore the existences of Grey-headed Lapwing. They saw the nest of Grey-headed Lapwing in unplowed area as many as 60% and they found the nest in plowed area (soil tillage) as many as 40%. Although Grey-headed Lapwing has great defense to attack the enemy, but they prefer breeding in safety place. In this case, when human activity do their work in soil tillage period, it can ruin the nests. It means that human activity is one of the factors that influencing the breeding success of Grey-headed Lapwing.